Inactivation of the lysine binding sites of human plasminogen (hPg) reveals novel structural requirements for the tight hPg conformation, M-protein binding, and rapid activation - Ayinuola, Yetunde A.; Castellino, Francis J. (Frontiers in Molecular Biosciences, 2023)
Accelerated activation of the human plasminogen zymogen (hPg) to two-chain active plasmin (hPm), is achieved following conformational changes induced by ligand-binding at the lysine-binding sites (LBS) in four of the five hPg kringle domains. In this manner, pattern D skin-trophic strains of Group A streptococci (GAS), through the expression of surface plasminogen-binding M-protein (PAM), immobilize surface hPg, thereby enabling rapid hPg activation by GAS-secreted streptokinase (SK). Consequently, GAS enhances virulence by digesting extracellular and tight cellular junctional barriers using hPm activity. Many studies have demonstrated the single importance of the kringle-2 domain of hPg (K2hPg) to PAM-binding using hPg fragments. Recently, we showed using full-length hPg, that K2hPg is critical for PAM binding. However, these studies did not eliminate any modulatory effects offered by the non-K2hPg LBS’ to this interaction. Moreover, we sought to establish the significance of the intramolecular interaction between Asp219 of the LBS of K2hPg and its serine protease binding partner, Lys708, to conformational changes in hPg. In the current study, selective inactivation of the LBS’ of K1hPg, K4hPg, and K5hPg, revealed that the LBS of these kringle domains are dispensable for hPg binding to PAM. However, the attendant conformational change upon inactivation of K4hPg LBS increased the affinity of hPg for PAM by an order of magnitude. This finding suggests that the native hPg conformation encloses PAM-binding exosites or sterically hinders access to K2hPg. While simultaneous inactivation of the LBS’ of K1hPg, K4hPg, and K5hPg inhibited hPg/SK association alongside hPg activation, the replacement of Lys708 generated a slight conformational change that optimally accelerated hPg activation. Thus, we accentuate disparate functions of hPg LBS and conclude using intact proteins that K2hPg plays the central role in regulating hPg activation